2023
DOI: 10.1002/ece3.10048
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and functional trait‐based community assembly within Pacific Cyrtandra (Gesneriaceae): Evidence for clustering at multiple spatial scales

Abstract: Tropical rainforest communities are often characterized by a small number of species‐rich genera that contribute disproportionately to the alpha diversity in these habitats. In the Pacific Basin, there are nearly 200 species of Cyrtandra, most of which are white‐flowered woody shrubs that are single‐island endemics. Within these island communities, multiple Cyrtandra species are commonly observed to occur sympatrically in wet forest understories, forming swarms of what appear to be ecologically similar taxa. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(115 reference statements)
0
2
0
Order By: Relevance
“…However, empirical evidence for intra-island community assembly is relatively scarce. A study on plants found evidence for clustering due to habitat filtering within islands (Johnson 2023), while dispersal limitation and stochasticity likely led to overdispersion of intra-island microbial communities (Wang et al 2020). On the contrary, our study detects no signals of community-wide functional and phylogenetic clustering or overdispersion of forest birds between contrasting habitats on the same island (Figure 3c).…”
Section: Structuring Of Bird Communities Within An Islandmentioning
confidence: 99%
“…However, empirical evidence for intra-island community assembly is relatively scarce. A study on plants found evidence for clustering due to habitat filtering within islands (Johnson 2023), while dispersal limitation and stochasticity likely led to overdispersion of intra-island microbial communities (Wang et al 2020). On the contrary, our study detects no signals of community-wide functional and phylogenetic clustering or overdispersion of forest birds between contrasting habitats on the same island (Figure 3c).…”
Section: Structuring Of Bird Communities Within An Islandmentioning
confidence: 99%
“…The potential for radiations to fill available niche space has been well documented (e.g., Gillespie, 2004). Incorporating ecological traits with denser phylogenetic sampling across different scales would allow testing of this hypothesis (Cerca et al, 2023;Johnson, 2023).…”
Section: Diversificationmentioning
confidence: 99%